LANGUAGE IDEOLOGY OF TEENAGERS TOWARD THE CATEGORIES OF GENDER IN LANGSA KOTA - Cut Kania Annissa Jingga Muti; Nisa Faradilla; Sarah Ziehan Harahap (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
ABSTRAKSociolinguistics is a study or discussion of language related to the language Sociolinguistics consists of two elements of the word that is socio and linguistics. Linguistics is the study of language, especially the elements of language (speech, word, sentence) and the relationship between speakers who are part of the members of society.Sociolinguistics places the position of language in relation to its use in society. This means that sociolinguistics views language as primarily a social system and communication system, and is part of a particular society and culture. Hence language and use of language are not observed individually but are always associated with their activities in society.Every human being born into the world is elected into two types, women and men. Gender refers to differences in male and female characters based on cultural construction, relating to the nature of their status, position, and role in society as well as socially-culturally constructed gender differences.In sociolinguistics, language and gender have a very close relationship. There is the phrase "why do women talk differently from men?" In other words, we are concerned with several factors that make women prefer to use standard language compared to men. In this regard, it is worth examining the language as a social part, a deed of value, reflecting the complexity of social networks, politics, culture, and age and society relations.language ideology is ideas and beliefs about what a language is, how it works and how it should work, which are widely accepted in particular communities and which can be shown to be consequential for the way languages are both used and judged in the actual social practice of those communities. In the community of western intellectuals, for instance, one key language ideology is inherited from the tradition of ideas whose major exponents include John Locke (in the Essay Concerning Human Understanding) and Ferdinand de Saussure (in the reconstructed and posthumously published work whose English translation is titled A Course in General Linguistics). In this tradition, signs (or words they are usually treated as being the same thing) stand for ideas, language is the means for conveying those ideas from one mind to another, and the process is underwritten by a sort of social contract, whereby speakers of a given language agree to make the same signs stand for the same ideas.